The alchemists : questioning our faith in courts as democracy-builders / Tom Gerald Daly, University of Melbourne. - Daly, Tom Gerald (Cambridge studies in constitutional law., 2017)
Can courts really build democracy in a state emerging from authoritarian rule? This book presents a searching critique of the contemporary global model of democracy-building for post-authoritarian states, arguing that it places excessive reliance on courts. Since 1945, both constitutional courts and international human rights courts have been increasingly perceived as alchemists, capable of transmuting the base materials of a nascent democracy into the gold of a functioning democratic system. By charting the development of this model, and critically analysing the evidence and claims for courts as democracy-builders, this book argues that the decades-long trend toward ever greater reliance on courts is based as much on faith as fact, and can often be counter-productive. Offering a sustained corrective to unrealistic perceptions of courts as democracy-builders, the book points the way toward a much needed rethinking of democracy-building models and a re-evaluation of how we employ courts in this role.